2010
DOI: 10.1371/journal.pone.0010549
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Targeted to the Brain with Image-Guided Focused Ultrasound Reduces Amyloid-β Plaque Load in the TgCRND8 Mouse Model of Alzheimer's Disease

Abstract: Immunotherapy for Alzheimer's disease (AD) relies on antibodies directed against toxic amyloid-beta peptide (Aβ), which circulate in the bloodstream and remove Aβ from the brain [1], [2]. In mouse models of AD, the administration of anti-Aβ antibodies directly into the brain, in comparison to the bloodstream, was shown to be more efficient at reducing Aβ plaque pathology [3], [4]. Therefore, delivering anti-Aβ antibodies to the brain of AD patients may also improve treatment efficiency. Transcranial focused ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
295
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 341 publications
(306 citation statements)
references
References 30 publications
(49 reference statements)
7
295
2
2
Order By: Relevance
“…This indicates that IC may be associated with the delivery of the reported antibodies and gene vectors, which was further supported by the observation of microhemorrhages and petechial hemorrhages in those studies that performed histologic analyses after FUS sonication. 5,33,35,36 The findings of our histologic analysis of mouse brains sonicated at 0.84 MPa ( Figure 5C) were consistent with the minor microscopic damaging effects reported in those studies. Behavioral tests performed in nonhuman primates after repeated FUS sonication in combination with MBs showed that the procedure did not cause functional damage even in the presence of minimal histologic damage, such as tiny clusters of extravasated red blood cells and a few dark neurons.…”
Section: Microbubble Cavitation Emissionssupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that IC may be associated with the delivery of the reported antibodies and gene vectors, which was further supported by the observation of microhemorrhages and petechial hemorrhages in those studies that performed histologic analyses after FUS sonication. 5,33,35,36 The findings of our histologic analysis of mouse brains sonicated at 0.84 MPa ( Figure 5C) were consistent with the minor microscopic damaging effects reported in those studies. Behavioral tests performed in nonhuman primates after repeated FUS sonication in combination with MBs showed that the procedure did not cause functional damage even in the presence of minimal histologic damage, such as tiny clusters of extravasated red blood cells and a few dark neurons.…”
Section: Microbubble Cavitation Emissionssupporting
confidence: 91%
“…[17][18][19][20] For the relatively larger-size dextrans (500 and 2,000 kDa), IC was found to be the main mechanism for their successful trans-BBB delivery. Cavitation detection has not been reported in previous studies of FUS-enhanced delivery of larger agents, such as antibodies 4,[32][33][34] and gene vectors, 5,35,36 whose MWs are on the same scale as the 500 and 2,000 kDa dextran, respectively. The MI of the FUS used in those studies varied within the range of 0.63 to 1.56, and the MI corresponding to 0.84 MPa (1.5 MHz) in our study was 0.69, which was in the lower end of the aforementioned range.…”
Section: Microbubble Cavitation Emissionsmentioning
confidence: 84%
“…The BBB can be transiently and selectively disrupted at the US focus without acute (Hynynen et al, 2001) or chronic neuronal damage or impact on the animal behavior (Howles et al, 2010). Transient changes in the BBB permeability open up new windows for noninvasive, targeted drug delivery in the central nervous system (Kinoshita et al, 2006a, b;Raymond et al, 2008;Jordao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…В работах J. Jordao и соавт. [62,63] было продемонстрировано, что воздействие ФУЗ увели-чивает накопление в мишени специфических антител к β-амилоиду и эндогенных антител в бляшках у трансген-ных мышей с болезнью Альцгеймера. После процедуры отмечено уменьшение количества и размера бляшек, а также активация глиальных клеток.…”
Section: локальное увеличение проницаемости гематоэнцефалического барunclassified